PENERAPAN METODE JARIMATIKA UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN BAGI ANAK TUNAGRAHITA RINGAN - Ekasanti, Ayu (Jurnal Pendidikan Khusus, 2017)
ABSTRACT. Short fingers and arithmetic method is a way of calculating mathematics using the fingers by opening and closing the fingers as the needed to do mathematical calculations. The purpose of this study was to improve light mentally retarded students’ acounting ability in nineth class of  SLB.C Kemala Bhayangkari 2 gresik. This research used a quantitative approach using one pretest-posttest group with O1 C O2 pattern. The result of this research showed there was influence of short fingers and arithmetic method to improve light mentally retarded students’ acounting in nineth class of  SLB.C Kemala Bhayangkari 2 gresik. The total of postive deviation score was 740, meaning that this method was effectively applied forlight mentally retarded students’ acounting where the final result of Tobserved 21.50>Ttable 2.57   Keywords : Short fingers and arithmetic method, multiplication ability